Fourth-generation folic acid active metabolite Quatrefolic® and micronized, microencapsulated iron Lipofer®: innovative approaches for iron and folic acid deficiencies in women (a review) - I.N. Kononova; E.N. Kareva (LCC «Medicine-Inform», 2022)
I.N. Kononova1, E.N. Kareva1,2  1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russian Federation To review up-to-date management algorithms for iron and folic acid deficiency in women of reproductive age, we selected relevant publications in the PubMed and Google Scholar databases (2012-2022). Current limitations of using peroral iron salts (malabsorption, poor adherence to treatment due to gastrointestinal adverse reactions, risks of oxidative stress, and ferroptosis resulting from iron overload) were prerequisites for developing innovative technology, Lipofer®. Lipofer® is a micronized and microencapsulated iron in a phospholipid coat which provides better absorption independent of hepcidin status and targeted iron delivery in tissues with minimization of adverse reaction risks. Limitations of using folic acid include low bioavailability in polymorphisms of folate cycle enzymes (dihydrofolate reductase/DHFR and methylenetetrahydrofolate reductase/MTHFR) which results in potential toxic effects of unmetabolized folic acid and abnormal homocysteine clearance (risk factors for vascular disorders and B12-deficiency anemia masking). These entities were prerequisites for the development of Quatrefolic®. Quatrefolic® is the glucosamine salt of (6S)-5-methyltetrahydrofolate, an active metabolite of folic acid with high solubility and bioavailability ready to enter the folate cycle without involving reductases. Quatrefolic® is safe and has no risks of overdosing or effects on B12-deficiency anemia diagnosis. A combination of two high-tech molecules is an innovative therapeutic tool for essential microelement requirements in women with high risks of iron and folic acid deficiencies. Keywords: iron-deficiency anemia, ferric pyrophosphate, microencapsulated iron, liposomal form, Lipofer, neural tube defect, folic acid, polymorphism, Quatrefolic, glucosamine salt. For citation: Kononova I.N., Kareva E.N. Fourth-generation folic acid active metabolite Quatrefolic® and micronized, microencapsulated iron Lipofer®: innovative approaches for iron and folic acid deficiencies in women (a review). Russian Journal of Woman and Child Health. 2022;5(1):18-27 (in Russ.). DOI: 10.32364/2618-8430-2022-5-1-18-27.